Traditional and Developing Segments of the Sharing Economy from the Point of View of Customers - Tetřevová, Liběna; Jelínková, Martina; Munzarová, Simona (Kaunas University of Technology, 2021)
The sharing economy represents a phenomenon which is increasing in importance as time goes by, even from the point of view of less developed countries. The aim of the study is to evaluate the knowledge of traditional and developing segments of the sharing economy and their platforms and to analyse and evaluate the level of their use employing the example of customers (the younger and the older generation) in one of the post-communist countries - the Czech Republic. Data was collected on the basis of a questionnaire survey (N=614). This was processed using descriptive statistics tools. The study shows that respondents are the most familiar with forms of sharing not only from traditional segments (passenger transportation and accommodation) but also from the financial segment. The best-known platforms include Uber, Airbnb and Zonky. Platforms from traditional segments are used the most. The younger generation has better awareness, both about possible forms of sharing and also about the existing platforms. However, the study did not prove any differences in the level of use of platforms between the younger and older generation.
Tradiční a rozvíjející se segmenty sdílené ekonomiky z pohledu zákazníků
Keywords: sharing economy; collaborative consumption; P2P Sharing; sharing accommodation; carpooling; sharing finances; sdílená ekonomika; kolaborativní spotřeba; P2P sdílení; sdílené ubytování; spolujízda; sdílení financí